2011
DOI: 10.1111/j.1440-1843.2011.01948.x
|View full text |Cite
|
Sign up to set email alerts
|

Interventional radiology of pleural diseases

Abstract: Image-guided pleural procedures are important in both the diagnosis and management of pleural disease. Pleural aspiration, biopsy and drainage are all proven to be safer and more efficacious using image guidance. The aim of this article is to review common imageguided pleural techniques and the evidence base for their application in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 131 publications
0
19
0
Order By: Relevance
“…It is believed that the choice between US and CT guidance is often influenced by factors such as individual preference, expertise, appliance availability, and cost [8,20]. These results suggest that both methods offer certain advantages.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It is believed that the choice between US and CT guidance is often influenced by factors such as individual preference, expertise, appliance availability, and cost [8,20]. These results suggest that both methods offer certain advantages.…”
Section: Discussionmentioning
confidence: 62%
“…We performed a prospective study comparing the safety and efficacy of CT scan-guided Abrams' needle pleural biopsy (CT-ANPB) and MT and observed that the two methods did not differ significantly with respect to both diagnostic sensitivity and complication rates [6]. US-assisted pleural biopsy performed using Tru-Cut needles (US-CNPB) has also been utilized frequently [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…The risk of complications is lower than with blind biopsy. 2,4,16,20 Although complications were not the primary focus of this study, serious complications, such as hemothorax or laceration of the spleen or kidney, did not occur in either group. The percentage of pneumothorax was higher in the ultrasound group, which might be in relation to the greater percentage of subjects with pleural effusion less than two thirds on chest radiograph.…”
Section: Discussionmentioning
confidence: 99%
“…Success with US-guided thoracentesis can be as high as 97%, while the incidence of pneumothorax is around 3%. 71 However, US may not reduce the incidence of intercostal vessel lacerations as vascular structures are often not identified sonographically, especially when they run medial to the angle of the rib. Advanced age and the performance of pleural procedures less than 7 cm from the spinous processes of thoracic vertebrae are risk factors for intercostal artery injury.…”
Section: Bronchoscopic Intervention and Imagingmentioning
confidence: 99%
“…Advanced age and the performance of pleural procedures less than 7 cm from the spinous processes of thoracic vertebrae are risk factors for intercostal artery injury. 71 Treatment for this complication is exploratory thoracotomy or, in poor surgical candidates, transcatheter arterial embolization using coils and polyvinyl alcohol particles. Radiofrequency ablation is a minimally invasive treatment for lung cancer in nonsurgical candidates and a palliative measure for intractable pain.…”
Section: Bronchoscopic Intervention and Imagingmentioning
confidence: 99%